The relation of education, occupation, and cognitive activity to cognitive status in old age: the role of physical frailty. (25th May 2017) - Ihle, Andreas; Gouveia, Élvio R.; Gouveia, Bruna R.; Freitas, Duarte L.; Jurema, Jefferson; Odim, Angenay P.; Kliegel, Matthias
ABSTRACT: Background: It remains unclear so far whether the role of cognitive reserve may differ between physically frail compared to less frail individuals. Therefore, the present study set out to investigate the relation of key markers of cognitive reserve to cognitive status in old age and its interplay with physical frailty in a large sample of older adults. Methods: We assessed Mini-Mental State Examination (MMSE) in 701 older adults. We measured grip strength as indicator of physical frailty and interviewed individuals on their education, past occupation, and cognitive leisure activity. Results: Greater grip strength, longer education, higher cognitive level of job, and greater engaging in cognitive leisure activity were significantly related to higher MMSE scores. Moderation analyses showed that the relations of education, cognitive level of job, and cognitive leisure activity to MMSE scores were significantly larger in individuals with lower, compared to those with greater grip strength. Conclusions: Cognitive status in old age may more strongly depend on cognitive reserve accumulated during the life course in physically frail (compared to less frail) older adults. These findings may be explained by cross-domain compensation effects in vulnerable individuals.